ROLE OF INTRALESIONAL VITAMIN-D IN VIRAL WARTS - Zainab, Zarnab; Malik, Naveed Akhtar; Obaid, Shanza; Mumtaz, Maimoona; Aftab, Kanza; Malik, Saqib; Pervaiz, Alia; Syed, Zainab (Journal of Ayub Medical College Abbottabad, 2021)
Seth D, Cheldize K, Brown D, Freeman EF. Global Burden of Skin Disease: Inequities and Innovations. Curr Dermatol Rep 2017;6(3):204-10. Kaushik M, Gupta S, Mahendra A. Living with Acne: Belief and Perception in a Sample of Indian Youths. Indian J Dermatol 2017;62(5):491-7. Sawada Y, Saito-Sasaki N, Mashima E, Nakamura M. Daily Lifestyle and Inflammatory Skin Diseases. Int J Mol Sci. 2021;22(10):5204. Published 2021 May 14. doi:10.3390/ijms22105204 Al Aboud AM, Nigam PK. Wart (Plantar, Verruca Vulgaris, Verrucae) [Updated 2019 Sep 27]. In: StatPearls [Internet]. Treasure Island (FL): StatPearls Publishing; 2020 Jan-. [cited 2020 May]. Available from: https://www.ncbi.nlm.nih.gov/books/NBK431047/ Information NC for B, Pike USNL of M 8600 R, MD B, Usa 20894. What are the treatment options for warts? [Internet]. InformedHealth.org. Institute for Quality and Efficiency in Health Care (IQWiG); 2019 [cited 2020 May]. Available from: https://www.ncbi.nlm.nih.gov/books/NBK279585/ Dall’oglio F, D’Amico V, Nasca MR, Micali G. Treatment of cutaneous warts: an evidence-based review. Am J Clin Dermatol 2012;13(2):73-96. Priya A, Adil M, Amin SS, Mohtashim M, Bansal R, Alam M. Intralesional Vitamin D3 in Recalcitrant Palmoplantar and Periungual Warts: A Prospective, Observational Study. Acta Dermatovenerol Croat 2019;27(4):215-24. Kavya M, Shashikumar BM, Harish MR, Shweta BP. Safety and Efficacy of Intralesional Vitamin D3 in Cutaneous Warts: An Open Uncontrolled Trial. J Cutan Aesthet Surg 2017;10(2):90-4. El-Taweel AE, Salem RM, Allam AH. Cigarette smoking reduces the efficacy of intralesional vitamin D in the treatment of warts. Dermatol Ther 2019;32(2):e12816. Riaz A, Riaz J, Ahmed W, Mushtaq R, Riaz O, Mushtaq K. Comparison of efficacy of cryotherapy versus oral zinc sulphate in the treatment of cutaneous warts. Pak Armed Forces Med J 2020;70(2):519-23. Raghukumar S, Ravikumar BC, Vinay KN, Suresh MR, Aggarwal A, Yashovardhana DP. Intralesional Vitamin D3 Injection in the Treatment of Recalcitrant Warts: A Novel Proposition. J Cutan Med Surg 2017;21(4):320-4. Liu J, Li H, Yang F, Ren Y, Zia T, Zhao Z, et al. Epidemiology and Clinical Profile of Cutaneous Warts in Chinese College Students: A Cross-Sectional and Follow-Up Study. Sci Rep 2018;8(1):15450. Shaldoum DR, HassanGFR, El Maadawy EH, El-Maghraby GM. Comparative clinical study of the efficacy of intralesional MMR vaccine vs intralesional vitamin D injection in treatment of warts. J Cosmet Dermatol 2020;19(8):2033-40. Prohaska J, Jan AH. Cryotherapy. In: StatPearls [Internet]. Treasure Island (FL): StatPearls Publishing; 2021 [cited 2021 May]. Available from: http://www.ncbi.nlm.nih.gov/books/NBK482319/ Salah E. Impact of multiple extragenital warts on quality of life in immune-competent Egyptian adults: a comparative cross-sectional study. Clin Cosmet Investig Dermatol 2018;11:289-95. Aman S, Nadeem M, Mahmood K, Ghafoor MB. Pattern of skin diseases among patientsattending a tertiary care hospital in Lahore, Pakistan. J Taibah Univ Med Sc 2017;12(5):392-6. Fathy G, Sharara MA, Khafagy AH. Intralesional vitamin D3 versus Candida antigen immunotherapy in the treatment of multiple recalcitrant plantar warts: A comparative case-control study. Dermatol Ther 2019;32(5):e12997. El Sayed MH, Sayed FS, Afify AA. Intralesional zinc sulfate 2% vs intralesional vitamin D in plantar warts: A clinicodermoscopic study. Dermatol Ther 2020;33(3):e13308.